Influência dos programas de reorientação da formação do profissional da saúde no processo de trabalho: perspectiva dos preceptores - Santos, Weslei Passos dos (2016)
To meet the needs of the new profile of health workers, arising from the new care model proposed by the National Health System, the Ministries of Health and Education signed a partnership and as strategies, built public policies to approach graduation the work process of services and consolidate changes in the training of these professionals. One such policy is the National Program for Reorientation of Vocational Training in Health (Pro-Health), created to guide the training of health professionals with emphasis on primary care and the other is the Education Program for Working for Health (PET- Cheers). The PET-Health has the focus in the Family Health Strategy (ESF) in order to promote the teaching-service-community integration, one of the pillars preceptorship health. This research analyzes the influence of the Pro and PET-Health at the primary care work process from the perspective of preceptors. The study included 43 professionals, nine of the ten health centers Family (CSF) participants in these programs, which performed the preceptor function. The data collection instrument was structured in two parts, the first being formed by demographic, professional and academic and the second part by a Likert scale consisting of 32 assertions distributed in four dimensions, which aimed to identify the perception of the respondents about the concept of health work process, the work process in primary care, the teaching-service partnership between the Pro and PET-Health and activities influenced by the Pro and PET-Health. Excel program for typing and data analysis was used. The results indicated that the participants had a satisfactory perception of those aspects related to the concept and the characterization of the work process in the FHS, but were more critical in their responses about the influence of the Pro and PET-health in primary care. Doctors, teachers, preceptors with ties to the PETHealth and those with more than three years in this role had good perception about the teaching-service partnership and the changes in the work process provided by the programs. We conclude that, despite the influence of the Pro and PET-Health have been perceived critically for some groups, the program consisted in an experience of great value, but the study shows the challenges that health services and institutions education have to motivate and provide equal conditions for the development of the work of all preceptors.